2020
DOI: 10.1158/1078-0432.ccr-19-1824
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Analyses of the SARC028 Trial Reveal an Association Between Sarcoma-Associated Immune Infiltrate and Response to Pembrolizumab

Abstract: Purpose: We recently reported a 17.5% objective RECIST 1.1 response rate in a phase II study of pembrolizumab in patients with advanced sarcoma (SARC028). The majority of responses occurred in undifferentiated pleomorphic sarcoma (UPS) and dedifferentiated liposarcoma (DDLPS). We sought to determine whether we can identify immune features that correlate with clinical outcomes from tumor tissues obtained pre-and on-treatment.Patients and Methods: Pretreatment (n ¼ 78) and 8-week ontreatment (n ¼ 68) tumor biops… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
122
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(128 citation statements)
references
References 42 publications
6
122
0
Order By: Relevance
“…In addition, densities of intratumoral CD8+ T cells at baseline correlated with a better progression-free survival. 21 GIST, a subtype that is mostly studied separately from other STS subtypes, was not included in the aforementioned clinical studies. In silico analyses using this STS subtype have demonstrated gene expression patterns associated with immune checkpoint inhibitor responses.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, densities of intratumoral CD8+ T cells at baseline correlated with a better progression-free survival. 21 GIST, a subtype that is mostly studied separately from other STS subtypes, was not included in the aforementioned clinical studies. In silico analyses using this STS subtype have demonstrated gene expression patterns associated with immune checkpoint inhibitor responses.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent profiling studies of immune checkpoints expression in STSs and bone sarcomas revealed their correlation with poor clinical outcomes and provide rationales for their targeting (Dancsok et al , 2019; Orth et al , 2020). In fact, a new study revealed a positive correlation between immune infiltration and response to anti‐PD‐L1 therapy in sarcoma (Keung et al , 2020). Similarly, a gene expression study in 608 tumors across STS subtypes established a classification between immune‐low, immune‐high, and vascularized phenotypes (Petitprez et al , 2020).…”
Section: Epidemiology Of Sarcomamentioning
confidence: 99%
“…Two landmark translational studies have now been published on the SARC028 trial of pembrolizumab, focused on UPS and DDLS. Baseline tumour biopsies indicated responders had higher infiltration of T lymphocytes and a higher percentage of PD-L1 + macrophages, as well as effector memory and regulatory T cells 15 . Petitprez et al carried out analyses across a number of STS cohorts, identifying five sarcoma immune classes with histological subtypes evenly distributed across the most immune rich classes.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcomas are not a single disease entity but rather a group of cancers with diverse biology and consequently diverse responses to therapy. There is evidence to suggest that patients with undifferentiated pleomorphic sarcomas (UPS) in particular may be more responsive to anti-PD-1 therapy than patients with other sarcoma subtypes 12,15 . Not only is UPS the most common subtype amongst patients with ESTS, it is also associated with the highest rates of systemic relapse and poorest survival outcomes 4 .…”
Section: Introductionmentioning
confidence: 99%